Pyoderma Gangrenosum: An Exceptional Complication of Venous access Device. Issue 4 (July 2014) - La Marca, Sophie; Toussoun, Gilles; Quoc, Christophe Ho; Sebban, Henry; Delay, Emmanuel
Introduction: Pyoderma gangrenosum (PG) is a rare disease whose precise etiology remains unknown. It causes rapidly developing skin necrosis and can occur after surgery, or after a nonspecific external stimulus. This condition is difficult to diagnose because it often mimics a fulminant infection. Clinical case: We present a case of very significant local presentation of PG after placement of a venous access device. Fifteen days after placement, the patient developed extensive cutaneous ulcers and necrosis in the subclavicular area, which led to the misdiagnosis of infection. The device was removed and the patient was given antibiotics. Because there was no improvement following antibiotic treatment, combined with the worrying and extensive appearance of the skin and extremely intense pain, the diagnosis of PG was made. The patient was immediately treated with high-dose corticosteroids, resulting in rapid improvement of the lesions and relief of pain. Conclusion: PG should be considered in cases of extensive, antibiotic-resistant ulceration and treatment with corticosteroids should be initiated. Clinical improvement is usually dramatic, with almost immediate suppression of the pain and arrest of the lesion's progression. Early treatment is the best guarantee for an effective recovery.